Strategi Komunikasi Penyuluh Agama Islam dalam Menjaga Toleransi Umat Beragama di Kecamatan Tempurejo Kabupaten Jember - Muhammad Ali Nasir; Kun Wazis (Maddah: Journal of Advanced Da'wah Management Research, 2022)
The point of this problem is the communication strategy of Islamic religious educators in maintaining religious tolerance in Tempurejo District, Jember Regency, because Islam teaches its people through teachings brought by the Prophet Muhammad regarding the importance of maintaining unity and harmony, both inside and outside Muslims. The focus of this research is as follows: 1) How is the Communication Strategy of Islamic Religious Counselors in Maintaining Religious Tolerance in Tempurejo District? 2) What are the inhibiting and supporting factors of the Communication Strategy of Islamic Religious Counselors in Maintaining Religious Tolerance in Tempurejo District? 3) What is the Communication Strategy of Islamic Religious Counselors in anticipating conflicts between religious communities in the Tempurejo District? The objectives of this study are: 1) Islamic Religious Counselors in fostering Islamic society the importance of maintaining tolerance between religious communities in Tempurejo District, Jember Regency. 2) What are the inhibiting and supporting factors for the communication strategy of Islamic Religious Counselors in fostering Islamic society, the importance of maintaining tolerance between religious communities in Tempurejo District, Jember Regency. From the results of this study, several conclusions can be drawn from the communication strategy efforts carried out by Islamic Religious Counselors in carrying out activities for fostering religious harmony in Tempurejo District, among others: Islamic Religious Counselors use communication in planning da'wah communication strategy activities in spreading tolerance and implications for Extension workers and the government of the Tempurejo District created an institution for religious harmony, because the institution could be used as a place to create and maintain religious harmony in the Tempurejo District.